2012
DOI: 10.4301/s1807-17752012000100005
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Management, Market Orientation, Innovativeness and Organizational Outcomes: a study in companies installed in Brazil

Abstract: This article analyzes the study of the relationship among knowledge management, the company's market orientation, innovativeness and organizational outcomes. The survey was conducted based on a survey held with executives from 241 companies in Brazil. The evidence found indicates that knowledge management directly contributes to market orientation, but it requires a clearly defined strategic direction to achieve results and innovativeness. It was also concluded that knowledge, as a resource, leverages other re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 49 publications
(112 reference statements)
1
5
0
1
Order By: Relevance
“…Reference [33] investigated the effects of three components of knowledge management namely knowledge acquisition, knowledge conversion and knowledge application on product innovation in Nigeria. Their results were consistent with previous findings by Reference [34] but inconsistent with that of Reference [35], who found that in small manufacturing firms, knowledge creation and storage has no impact on their ability to innovate and also with Reference [36] who reported that knowledge management which include KA does not impact product innovation except when moderating for strategic orientation. No specific empirical certainty regarding the degree and the mechanism through which KA influences PIF in the Malaysian manufacturing sector has been reported, as such warrants investigation.…”
Section: Knowledge Acquisition (Ka) and Product Innovation Flexibilitsupporting
confidence: 44%
“…Reference [33] investigated the effects of three components of knowledge management namely knowledge acquisition, knowledge conversion and knowledge application on product innovation in Nigeria. Their results were consistent with previous findings by Reference [34] but inconsistent with that of Reference [35], who found that in small manufacturing firms, knowledge creation and storage has no impact on their ability to innovate and also with Reference [36] who reported that knowledge management which include KA does not impact product innovation except when moderating for strategic orientation. No specific empirical certainty regarding the degree and the mechanism through which KA influences PIF in the Malaysian manufacturing sector has been reported, as such warrants investigation.…”
Section: Knowledge Acquisition (Ka) and Product Innovation Flexibilitsupporting
confidence: 44%
“…Notably, to fulfil market demands in a satisfactory manner, it is fundamental to promote inter-functional coordination, integrating and sharing internal information and practices associated with client and market management (Ferraresi, Santos, Frega, & Pereira, 2012). This result cannot be reached without the processes executed with the aim to sustain a value strategy (Mintzberg, Ahlstrand, & Lampel, 2010).…”
Section: Clients and Marketmentioning
confidence: 98%
“…De uma forma específica, o marketing visa assegurar que as capabilidades de uma organização sejam compatíveis com as evoluções do ambiente em que opera (DAY, 1994;HOOLEY;SAUNDERS;PIERCE, 2001). Sua finalidade é capacitar uma organização para se diferenciar, adaptar-se às evoluções do ambiente e dos clientes, além de desenvolver atributos críticos para sua sobrevivência (BETTIOL; DI MARIA; FINOTTO, 2011;FERRARESI et al, 2012).…”
Section: Marketing E Orientação Para Mercado Nas Médias Empresasunclassified